2016
DOI: 10.1111/ijfs.13058
|View full text |Cite
|
Sign up to set email alerts
|

Quality and safety of irradiated food regarding biogenic amines: Ras cheese

Abstract: Summary Food safety and quality became very important, especially with the challenge to ensure safe and healthy foods in regard to chemical hazards. So, this study was conducted to evaluate the quality and safety of irradiated Ras cheese during the storage period, with respect to biogenic amines (BAs). Ras cheese was manufactured, ripened and irradiated by γ‐irradiation at 0, 5, 10 and 15 kGy. The samples were stored in refrigerator at 5 ± 1 °C from where samples were withdrawn at 0, 2, 4 and 6 months for anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…Furthermore, the observed reduction was found to be proportional to both the irradiation dose and the storage time. The recorded loss in the moisture content, could be due to the decrease in the water-holding capacity of casein as reported by Shalaby et al, (2016). This reduction is also proportional to both the…”
Section: Radiation Effects On the Physicochemical Propertiessupporting
confidence: 54%
“…Furthermore, the observed reduction was found to be proportional to both the irradiation dose and the storage time. The recorded loss in the moisture content, could be due to the decrease in the water-holding capacity of casein as reported by Shalaby et al, (2016). This reduction is also proportional to both the…”
Section: Radiation Effects On the Physicochemical Propertiessupporting
confidence: 54%
“…Recent studies have also proved the effectiveness and safety of a high irradiation dose (>15 kGy) for ready‐to‐eat meat products, and a low irradiation dose (1–3 kGy) for fresh mushrooms (Fernandes et al ., ; Feliciano et al ., ). Irradiation technology is also a useful sterilisation method for its potential role for prolonging shelf‐life by controlling food‐borne diseases and spoilage and the willingness to pay for processing for food safety (Tomac & Yeannes, ; Stratakos & Koidis, ; Shalaby et al ., ). However, some previous studies have reported that irradiation treatment can change the colour of fresh meat and cause a characteristic unpleasant odour because of the myoglobin molecule and some of polyunsaturated fatty acids to energy input and alterations in the chemical environment, as well as could affect the functional properties of the food matrix, such as whole wheat flour and rice (Bashir et al ., ; Li et al ., ).…”
Section: Nonthermal Processing Technologiesmentioning
confidence: 97%
“…Although no legal status exists regarding the irradiation of fermented foods, including dairy products, many studies have demonstrated the effectiveness of irradiation in reducing the BA content in such foods. Exposure of various cheese types to 1 to 6 kGy of γ irradiation reduces the microbial counts and BAs in a dose‐dependent manner (Aly and others ; Shalaby and others ). However, concerns have been raised with regard to possible adverse effects on the nutritional quality of foods after irradiation.…”
Section: Biosynthesis Pathways Of Basmentioning
confidence: 99%
“…Nonetheless, doses below 6 kGy were shown to affect neither the chemical composition nor the gustatory quality of dairy products while reducing BA contents and microbial counts to different extents (Aly and others ). In fact, the treatment of Ras cheese (an Egyptian hard‐ripened cheese) with different doses of γ radiations (5, 10, and 15 kGy) reduced its BA content and microbial counts, and improved its gustatory quality after 6 mo of storage at 5 °C (Shalaby and others ). Therefore, the irradiation of dairy products may be especially useful in cheese where it can be applied after ripening to reduce BA content and, at the same time, prevent over‐ripening of some cheese varieties where it concomitantly reduces the microbial counts.…”
Section: Biosynthesis Pathways Of Basmentioning
confidence: 99%